Comparison of Tree Species Diversity and Usage by Ratufa indica indica in Umblebyle Range Forest, Bhadravathi Division, Shimoga, Karnataka, India - Venkatesh, Hamsa Rekha; Alavandi, Shwetha (Asian Journal of Biological and Life Sciences)
Ratufa indica is an arboreal top canopy-dwelling species endemic to India. Tree species diversity of a forest plays an important role in the survival of arboreal species including Ratufa indica, hence the study was designed to analyze the tree species diversity of dry deciduous forests of the Umblebyle Range, Shimoga, Karnataka. The study was carried out using line transect methodology surveying 20 transects walking a total distance of 47.7 km of trees covering an area of 8350.89 ha. A total of 77 tree species belonging to 31 families were identified. Nest tree preferences were assessed through the observation of 406 and 455 dreys (nests) on 385 and 415 nesting trees belonging to 20 and 22 families in the year 2021 and 2022 respectively. The animal was found to use the most abundant families and tree species 47 among 77 tree species were used for nesting, Fabaceae and Terminalia paniculata were the most preferred family and tree species, further deciduous trees were most preferred over others. The tree species diversity influences the nesting tree species diversity of the animal maintaining tree species diversity not only aids the conservation of animals in their habitat but also aids in the conservation of the forests
Keywords: Dreys; Nesting; Oriental Giant Squirrels; Ratufa indica; Tree species diversity; Umblebyle Range forest